2013
DOI: 10.1111/ans.12350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of appendicectomy outcomes: acute surgical versus traditional pathway

Abstract: Introduction: The acute surgical unit (ASU) is an evolving novel concept introduced to address the challenge of maintaining key performance indicators (KPIs) in the face of an increasing acute workload. Results:Our results show significant improvement in length of stay (2.8 days, 2.6 days, P = 0.0001) and proportion of daytime operations (59.4%, 65.8%, P = 0.004), in keeping with other studies on benchmarking. Conclusion:The introduction of ASU has led to significant improvements in some KPIs for appendicecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Hospital LOS was assessed in 19 studies. 10,[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][29][30][31] This measure was generally not clearly defined in these studies. Of the 8 studies that provided definitions, 4 looked at the time interval from inpatient admission to discharge, 3 considered the time from triage to discharge, and 1 mea sured emergency department arrival to discharge.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Hospital LOS was assessed in 19 studies. 10,[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][29][30][31] This measure was generally not clearly defined in these studies. Of the 8 studies that provided definitions, 4 looked at the time interval from inpatient admission to discharge, 3 considered the time from triage to discharge, and 1 mea sured emergency department arrival to discharge.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[4][5][6][7]14 Complication rates were reduced 5 or unchanged. 6,14 For non-elective cholecystectomy, wait times to surgery and lengths of stay were usually reduced following the implementation of an ACS model, 10,15 although most studies reported no difference in the complication rate. 9,10,15 Most studies used a repeated cross-sectional design to assess the immediate impact of implementing an ACS model, but few have provided data on whether these outcomes have endured.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have demonstrated a reduction in after‐hours or overnight operating . For non‐elective appendicectomy, wait times to surgery and lengths of stay were either reduced or unchanged, as were rates of perforated appendicitis . Complication rates were reduced or unchanged .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many previous reports have clearly demonstrated that the introduction of ASUs has led to significant improvements in the key performance indicators for appendicectomy including length of stay, mean time to theatre, proportion of day time operations and lower complication rates compared with the traditional care pathway. 7,8 However, this current analysis of and breakdown of the component costs of caring for acute appendicitis does offer valuable information which can be used at an institutional level to help improve overall efficiencies in management. Such measures might include improving access to the operating theatre particularly on weekends and reducing theatre turnaround time, and it could even be argued that there should be more consultant-led appendicectomies to reduce theatre operating times, although this obviously needs to be balanced against the requirements for registrar training and operative experience.…”
mentioning
confidence: 99%